2016
DOI: 10.5114/kitp.2016.62195
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of unfavorable prognosis for out-of-hospital sudden cardiac arrest in Bielsko-Biala district

Abstract: IntroductionThe prognosis in out-of-hospital sudden cardiac arrest (OHCA) remains unfavorable and depends on a number of demographic and clinical variables, the reversibility of its causes and its mechanisms.AimTo investigate the risk factors of prehospital death in patients with OHCA in Bielsko County.Material and methodsThe study analyzed all dispatch cards of the National Emergency Medical Services (EMS) teams in Bielsko-Biala for the year 2013 (n = 23 400). Only the cards related to sudden cardiac arrest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…Wibrandt et al [6] reported that VT/VF as initial rhythm, the cardiac etiology of OHCA and time to ROSC < 20 min were strong predictors of both survival and favourable neurological outcomes. In a recent Polish study on pre-hospital death predictors in OHCA victims, Gach et al [9] reported that univariate analysis indicated 6 predictors of death: OHCA without witnesses, OHCA in a public place, no bystander CPR, no bystander cardiac massage, initial diagnosis of non-shockable cardiac rhythm and the amount of drugs used for CPR. However, logistic regression confirmed that only the lack of bystander cardiac massage and non-shockable…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wibrandt et al [6] reported that VT/VF as initial rhythm, the cardiac etiology of OHCA and time to ROSC < 20 min were strong predictors of both survival and favourable neurological outcomes. In a recent Polish study on pre-hospital death predictors in OHCA victims, Gach et al [9] reported that univariate analysis indicated 6 predictors of death: OHCA without witnesses, OHCA in a public place, no bystander CPR, no bystander cardiac massage, initial diagnosis of non-shockable cardiac rhythm and the amount of drugs used for CPR. However, logistic regression confirmed that only the lack of bystander cardiac massage and non-shockable…”
Section: Discussionmentioning
confidence: 99%
“…Sensitivity rhythm were independent determinants of prehospital death [9]. Among other recent reports, Aldhoon et al [10] examined the factors affecting 1-month outcomes in 46 OHCA survivors treated with hypothermia.…”
Section: -Specicitymentioning
confidence: 97%
“…Recent registry-based studies provided much data on epidemiology, characteristics, and prehospital outcomes of patients with OHCA in Poland [2][3][4][5][6][7][11][12][13][14][15][16][17]. Howev-Table III.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years the number of studies on the epidemiology of OHCA in Poland has multiplied [2][3][4][5][6][7]. These studies have yielded a large amount of information on the incidence rate of OHCA and prehospital outcomes in the Polish population.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis revealed that patients with favorable outcomes (CPC 1 and 2) had an average SWAP score of 1, while patients with unfavorable outcomes (CPC 3, 4, 5) had an average SWAP score of 1.55. Among the total of 116 patients, 7 individuals (6.03%) survived with positive neurological outcomes (CPC 1 and 2), while 109 patients (93.96%) experienced poor neurological outcomes (CPC 3,4,5, and mortality). Conclusions: Patients who had a high SWAP score had a reduced likelihood of survival and sustained ROSC.…”
mentioning
confidence: 99%